Los organizadores gráficos, como estrategia metodológica para el aprendizaje, en el área de ciencias naturales - Ramón Ordóñez, Fabricio Clodovino (2016)
This research titled graphic organizers, as a methodological strategy for learning in the area of natural sciences, with sixth graders sub Basic level Media, School of General Education Basic Adolfo Jurado Gonzalez the Sagrario parish Loja City Academic Period 2014-2015, overall objective was to determine the importance of graphic organizers as methodological strategies for learning in the area of natural sciences in children sixth grade of General Basic Education School “Adolfo Jurado González “the Sagrario Parish, City Loja, during the academic year 2014-2015, research was pre-experimental and cross of explanatory and field; in which methods were used: synthetic analytic; inductive-deductive; Descriptive statistics; comprehensive; descriptive that allowed the collection and analysis of information obtained through techniques such as direct observation and survey of teaching; and, through the instrument of questionnaire applied to students, allowing justify the topic in the research work involved thirty students and a teacher. After obtaining the results showed that most students are unaware of the concept that is a methodological strategy; also they say they do not know they are graphic organizers, nor the importance of providing each of them; thus it can be concluded that the application of the graphic organizers as methodological strategies for learning proved to be one of the most efficient ways to achieve learning. Therefore it is recommended to use teaching strategies and activities that help to strengthen student learning, and thus putting into practice the values inside and outside the classroom.